Whose Pain Matters? Racial Differences in Perceptions of Emotional Pain After Fatal Police Shootings - Kahn, Kimberly Barsamian (Race and social problems, 2024)
Two studies examine whether target or participant race affect perceptions of emotional pain of perpetrators and victims of fatal police shootings, their associated networks (family, community), and how these perceptions influence incident-related outcomes. Study 1 utilized an experimental vignette about a police shooting of an unarmed Black or White teenager and tested perceived emotional pain and needs for the victim’s mother, family, and community. Results found perceptions of emotional pain and support needs were greater for Black compared to White mothers, families, and communities. However, participants were not more likely to want to provide support to Black mothers or families. Using data from the affected community after a real-world fatal police shooting, Study 2 provides complementary analyses of perceived emotional outcomes for the police officers and Black victim, and each of their networks. In Study 2, White participants, compared to racial minorities, thought police officer perpetrators and their families had more emotional pain and support needs after a fatal police shooting. While the pain of Black social networks was generally recognized, Social Dominance Orientation closed the gap between perceptions of emotional pain for the officers in relation to that of the victim’s network, which then predicted greater support for police behavior and less desire for officer accountability. These studies suggest that the public may recognize the differentially traumatic affect that police violence has on Black victims’ social networks, but whose pain is relatively focused on (victim vs. officer) affects perceptions of fatal police shootings and whether police accountability is desired.